Editorial: Special Issue “Molecules from Side Reactions II” - Stefano D’Errico; Annalisa Guaragna (Molbank, 2023)
This Special Issue, “Molecules from Side Reactions II”, belongs to the section Organic Synthesis of the journal Molbank and was launched in 2021, after the first edition, “Molecules from Side Reactions” [...]